Black Spots in Kerala's Socio-Economic Scene - A K PAT (Economic and Political Weekly June 11, 2005, 2005)
Kerala now enjoys a high rate of economic growth and remittances continue to boost consumption. But going by a number of socioeconomic indicators - such as farm production, unemployment, incidence of lifestyle diseases and suicides - the state is no god's own country.